Influence of splinting materials (auto vs. photopolymerizing) on implant impression accuracy: an in vitro study - Braz, Luís Miguel Baptista (2017)
Tese de mestrado, Medicina Dentária, Universidade de Lisboa, Faculdade de Medicina Dentária, 2016